Investigation of Biosynthetic Precursors of 3‑Isobutyl-2-Methoxypyrazine Using Stable Isotope Labeling Studies in Bell Pepper Fruits (Capsicum annuum L.) - Zamolo, Francesca; Wüst, Matthias (Journal of agricultural and food chemistry, 2022)
The biosynthesis of 3-isobutyl-2-methoxypyrazine (IBMP) in bell pepper fruits (Capsicum annuum L.) was investigated by in vivo feeding experiments with stable isotope-labeled precursors. Volatiles were extracted using headspace solid-phase microextraction (HS-SPME) and analyzed by comprehensive two-dimensional gas chromatography (GC×GC) coupled to a time-of-flight mass spectrometer (ToF-MS). Feeding experiments revealed incorporation of l-leucine and α-ketoisocaproic acid (α-KIC) as well as glycine and glyoxylic acid into IBMP. Furthermore, it has been shown that de novo biosynthesis of IBMP occurs in pericarp tissues of unripe bell pepper fruits, whereas pericarp tissues of ripe bell pepper fruits showed no capability of IBMP biosynthesis.